2005
DOI: 10.1117/12.622677
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the degradation mechanisms in high-power diode lasers using multi-channel micro-thermography

Abstract: We demonstrate the applicability of imaging thermography for investigations of mechanisms associated with gradual degradation in diode lasers. The introduction of two spectral channels provides the means for separate observation of deep level luminescence and thermal radiation emitted according to Planck's law. In the near IR region we found the signal detected by the camera to be mainly affected by mid-gap deep-level luminescence. An intensity increase of the luminescence signal for an aged diode laser compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We found that signals detected in this spectral channel are mainly caused by mid-gap deep-level luminescence. 4,5 A comparison between a new DL and a DL aged for 3000 hourssee Figure 3(a,b) and (c,d) respectively-shows that, over time, the intensity of this type of luminescence increases in the near IR. Most probably, the concentration of deep-level defects increases during aging.…”
Section: Figure 3 Front View Thermographic Images Acquired In the Nementioning
confidence: 99%
See 2 more Smart Citations
“…We found that signals detected in this spectral channel are mainly caused by mid-gap deep-level luminescence. 4,5 A comparison between a new DL and a DL aged for 3000 hourssee Figure 3(a,b) and (c,d) respectively-shows that, over time, the intensity of this type of luminescence increases in the near IR. Most probably, the concentration of deep-level defects increases during aging.…”
Section: Figure 3 Front View Thermographic Images Acquired In the Nementioning
confidence: 99%
“…On the other hand, re-absorption of light at the defect centers gives rise to increased heating, which was examined in the mid-IR range. 5 The temperature increase as a result of long-term operation certainly limits the performance of the device. Summarizing, we have used a micro-thermographic method to investigate effects responsible for both fast and slow degradation of diode lasers.…”
Section: Figure 3 Front View Thermographic Images Acquired In the Nementioning
confidence: 99%
See 1 more Smart Citation